IDENTIFICATION OF AQUIFER LAYERS USING THE ELECTRICAL RESISTIVITY TOMOGRAPHY (ERT) METHOD IN GUNUNG KASIH AREA - Alviyanda, Alviyanda; Farduwin, Alhada; Nugraha, Purwaditya; Widiatama, Angga Jati; Natalia, Happy Christin; Ogara, Evan Rosyadi; Piqri, Hafidz (Engineering Faculty Universitas Lampung, 2025)
The varied physiographic conditions of Lampung, from the west to the center and east, are the main factors in determining the geological field campus as a suitable learning environment. Gunung Kasih is one of the areas located on the Bukit Barisan Range, which has unique geological conditions with exposed basement rocks on the surface, making it a key factor in determining the geological field campus. However, the presence of crystalline basement rocks in Gunung Kasih prevents water from penetrating below the surface, thereby affecting the availability of groundwater for the local community. This study aims to identify aquifer layers around the Gunung Kasih area, using the Electrical Resistivity Tomography (ERT) method. Stratigraphically, based on field observations of rocks, the study area has lithology consisting of schist, marble, and sandstone in the western part, with a landscape characterised by structural hills. On the eastern side, volcanic deposits such as tuff and andesitic lava were found, with a denudational plain landscape. The geophysical survey was conducted using Wenner-Schlumberger configuration, with four survey lines oriented relatively west to east and north to south. Low resistivity anomalies are indicated by layers with resistivity values of 0–20.7 Ωm, while moderate-to-high anomalies have resistivity values of 29.9–89.9 Ωm. Very high resistivity anomalies are indicated by layers with resistivity values of 61.9–128 Ωm. In comparison with observations of rock outcrops and rock resistivity values, the aquifer layer is interpreted as being indicated by low resistivity anomalies in the relatively eastern part of the study area, which is near the surface to a depth of 15 metres and 25 metres. This layer is interpreted as tuffaceousrock comparable to the Hulusimpang Formation. The aquifer layer in the study area is interpreted as a shallow unconfined aquifer.